Republic of San Marino : 2009 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice; and Statement by the Executive Director for the Republic of San Marino. (IMF Staff Country Reports; Country Report ;, 2010)
This 2009 Article IV Consultation highlights that the global financial crisis, which began to affect the economy of San Marino in the second half of 2008, is likely to continue to do so in 2009-10. Short-term vulnerabilities in the financial sector have risen owing to exposure of the largest bank to a troubled Italian banking group and to liquidity pressures from a tax amnesty adopted by the Italian government. Executive Directors have commended the authorities for strengthening international cooperation in economic and financial matters.